Palliative care at the end of life in pediatric oncology: a nursing perspective - Tatiana Pifano da Silva; Liliane Faria da Silva; Emília Gallindo Cursino; Juliana Rezende Montenegro Medeiros de Moraes; Rosane Cordeiro Burla de Aguiar; Sandra Teixeira de Araújo Pacheco
ABSTRACT Objectives: To identify the knowledge of nursing professionals about palliative care in pediatric oncology and their needs for end-of-life care. Method: A descriptive study with a qualitative approach, carried out in a federal hospital in Rio de Janeiro specialized in oncology. 29 nursing professionals from the pediatric inpatient sector participated in semi-structured interviews between July and August 2019. Data submitted to textual lexicographic analysis with Iramuteq. Results: Professionals are aware of the use of comprehensive care, centered on the family, aimed at comfort, and dignified death. They highlighted the need for psychological support for the nursing team, in addition to effective communication with a multidisciplinary team and carrying out actions for professional training in pediatric palliative care. Final considerations: A study showed care that is consistent with the precepts of palliative care and points out gaps in training, highlighting the need for professional training with a view to quality care.